PROMOSI SMK MUHAMMADIYAH 05 KARANGGEDE DALAM MENINGKATKAN DAN MEMAKSIMALKAN PPDB - Kusno Hariyoko; Ahmad Muhibbin (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2023)
School promotion is an effort carried out by certain parties as an effort to promote or introduce the school to the surrounding community. The aim of this school promotion work program is to increase the school's PPDB and promote the school to the wider community so that they want to register their children as prospective students at SMK Muhammadiyah 5 Karanggede. The implementation method used in this service is the qualitative method and the diffusion method science and technology. The data collection techniques used were observation interviews and documentation. The school promotion work program is carried out through outreach, making PPDB pamphlets and installing billboards as a forum for promoting vocational schools around Karanggede. It is hoped that the school will get the results of this school promotional activity increase in PPDB